Evaluation of rs1982073 polymorphism of transforming growth factor-β1 in glioblastoma - Sadeghi, Yasaman (J Res Med Sci, 2019)
BACKGROUND: Glioblastoma (GBM) is the most common and invasive form of primary malignant brain tumors, with a survival rate of about 1 year. Transforming growth factor-β1 (TGF-β1) plays a very important role in tissue homeostasis and cancers. It seems that polymorphism of T29C (L10P, rs1982073, or rs1800470), which has been studied in various cancers such as breast and colon, creates the significant differences plays an important role in GBM prognosis and treatment. In this study, we evaluated the effect of T29C (rs1982073) polymorphism of TGF-β1 gene in GBM. MATERIALS AND METHODS: This study was conducted on 100 cases of GBM including 47 paraffin-embedded brain tissue samples and 53 blood samples from another 53 GBM patients, who was under therapy, and 150 were controls. The TGF-β rs1982073 single-nucleotide polymorphism (SNP) was identified by the NCBI and genotyping was performed by high-resolution melt (HRM) assay. Melt curves from HRM which suspected to SNP were selected and subjected to direct sequencing. Finally, the collected data were entered into the SPSS software (Version. 20) and mean ± standard deviation or n (%) was used to show the data. RESULTS: The mean age in GBM group was 51.63 ± 13.27 years. Accordingly, the two groups were matched in terms of age and gender (P > 0.05). The frequency of GG genotype was significantly higher in GBM patients. In contrast, although the frequency of AG genotype was higher in GBM group, it was not statistically significant. Furthermore, the presence of G allele was significantly more frequent than A allele in GBM patients. CONCLUSION: Findings of the present study supports that the Pro10Leu, rs1982073, or rs1800470 SNP in TGF-β1 is found to be expressed significantly more in GBM patients as it was found in breast cancer.